ANALISIS PERAN PEKERJA SOSIAL DALAM PENANGANAN ANAK KORBAN KEKERASAN SEKSUAL DI KOTA BENGKULU - Siregar, Rosi L. Vini; Afrita, Desy (Jurnal Ilmiah Widya Sosiopolitika, 2021)
ABSTRACT Sexual violence experienced by children can have an impact on the physical, psychological and social conditions of children that affect the growth and development of children in the future. On that basis, handling child victims of sexual violence requires the role of various parties, including social workers. Child social workers aim to provide assistance, rehabilitation, and protection of children's rights. The purpose of this study seeks to describe the roles and obstacles in dealing with child victims of sexual violence in Bengkulu City. This study uses a descriptive qualitative approach, with 5 informants using interview, observation and documentation studies. The results showed that the role of social workers in dealing with child victims of sexual violence could be in the form of facilitator, broker, initiator, protector, and advocate. There are five inhibiting factors in carrying out the role: (a) Barriers in funding (b) lack of facilities and infrastructure related to protection, (c) social welfare service centers that are not yet available (d) lack of professional human resources in dealing with children's problems, (e) Limited networks make it difficult for social workers to refer victims of child sexual abuse to clinical psychologists. Keywords: Role, Social Worker, Child Victim of Sexual Violence